Functional dyspepsia and gastroparesis: are they distinct disorders, a spectrum of diseases or one disease? - Simon Keely; Nicholas J Talley; Michael Potter; Kerith Duncanson; Stella-Maris Egboh (eGastroenterology)
Functional dyspepsia (FD) and gastroparesis (GP) are clinically managed as distinct upper gastrointestinal conditions but present with symptoms that are often indistinguishable. FD is a common disorder of gut–brain interaction that negatively impacts quality of life, while GP is considered a rare disease exclusively defined by delayed gastric emptying and symptoms. The degree of overlap between these disorders makes them hard to differentiate in clinical practice, thereby impacting treatment decisions. This review is focused on exploring the similarities and differences between FD and GP to guide clinician management and improve treatment outcomes. A comprehensive literature search was performed and the full texts of eligible articles were retrieved for the extraction of information reported in this review.This summary of evidence supports the hypothesis that GP and FD represent two ends of the same disease spectrum in a major subgroup. Improved understanding of the similarities, differences and overlap is likely to help guide the development of objective biomarkers and better-targeted therapies.